Landscape semiotics and visual / textual analysis in Anglo-American cultural geography - Roman Lozynskyi (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2020)
The article focuse is on the landscape understanding from the perspective of semiotics and critical social theory in Anglo-American cultural geography and the method of landscape visual/textual analysis. The history of approaches to landscape understanding and research in Anglo-American cultural geography from the beginning of the XX century to this day is analyzed, as well as the consideration of the landscape in the European Landscape Convention. It was found that the use of the concept of landscape in human geography primarily implies the emphasis on the visual aspect of the built environment. It was found that from the perspective of semiotics, landscapes, in addition to the material (physical) dimension, carry a semantic load, convey meaning, are a system of signs and can be read as text. The axioms for reading the landscape of American geographers P. Lewis and D. Mitchell, and ideas of structuralist semiotics are presented. These theoretical and methodological approaches are applied to study the architectural styles of administrative, residential and commercial buildings, monuments and advertisement in public space, place names and other ways of symbolic marking of space as well as landscapes representation in the media (movies, news, advertisements, paintings, literature). The article also examines the understanding of the landscape from the perspective of critical social theory, according to which they are involved in the construction, maintenance, legitimization and resіstence of social structures (systems of relations), such as national, political, economic, class or gender. The approaches to landscape research discussed in the article are central to the analysis of visual changes of built environment in urban and rural settings, including the process of "decommunization" in Ukraine, landscape involvement in capitalist relations and consumption practices, it commodification and commercialization. It was found that landscapes visual/textual analysis also allows to reveal the values and identities of people expressed in the architectural styles of single-family houses. The application of the considered approaches is important for the improvement of urban planning and architectural regulations in order to create a socially just environment, taking into account the historical, social and cultural context, and the needs of different residents.